Design and Implement a Wheelchair by Moving the Head of People Who are Paralyzed: Merancang dan Mengimplementasikan Kursi Roda dengan Menggerakkan Kepala Orang yang Lumpuh - Kadhim, Mohammed Sameer; Kamil, Mustafa Majid; Kadhum, Ruqaya Dhyaa; Mahmoud, Mustafa (Procedia of Engineering and Life Science, 2024)
General Background: Wheelchairs play a crucial role in enhancing mobility for individuals with disabilities, illness, or injury, with various designs tailored to meet specific needs. Specific Background: Among these, powered and manual wheelchairs serve distinct functions, with recent technological advancements promising improved user experience. Despite innovations, the market often struggles with overspecialization, leaving gaps in accessibility and usability, particularly for populations in developing regions. Knowledge Gap: While advancements like the Leveraged Freedom Chair and geared manual wheels have emerged, there remains a lack of comprehensive integration of modern technologies to enhance performance across diverse environments. Aims: This study aims to evaluate the technological evolution of wheelchairs, specifically focusing on design improvements and user-centric innovations, alongside the development of a prototype utilizing Arduino Nano and supporting components for enhanced functionality. Results: The findings indicate that integrating components such as the IBT-2 motor driver, MPU6050 motion sensors, and effective power management systems significantly improves maneuverability and adaptability of wheelchairs, particularly for users with tetraplegia. Novelty: The study presents a novel approach in wheelchair design that incorporates advanced microcontroller technology to facilitate independent mobility, thereby addressing limitations in traditional wheelchair functionality. Implications: The research contributes to the field of assistive technology by demonstrating that enhanced wheelchair designs not only promote physical mobility but also improve the overall quality of life for users, highlighting the importance of continued innovation and accessibility in wheelchair technology for diverse populations. Highlights: User-Centric Design: Tailoring features to meet individual user needs. Technological Integration: Enhancing functionality with advanced components like Arduino Nano. Quality of Life: Improved designs enhance independence and overall well-being. Keywords: wheelchair technology, tetraplegia, assistive devices, microcontroller, mobility innovation